2021
DOI: 10.1016/j.ccell.2020.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Proteogenomic insights into the biology and treatment of HPV-negative head and neck squamous cell carcinoma

Abstract: Highlights d A systematic inventory of HNSCC-associated proteins, phosphosites, and pathways d Three multi-omic subtypes linked to targeted treatment approaches and immunotherapy d Widespread deletion of immune modulatory genes accounts for loss of immunogenicity d Two modes of EGFR activation inform response to anti-EGFR monoclonal antibodies

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
190
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 237 publications
(201 citation statements)
references
References 153 publications
11
190
0
Order By: Relevance
“…In contrast to the high fraction of protein overexpression, only 25% of samples in the TCGA-HNSC cohort were identified to have an active EGFR pathway. A recent phosphoproteomic study in HNSCC has identified that EGFR ligands rather than the receptor are the rate-limiting factor for EGFR pathway activity, offering an explanation for this discordance (33). This could be an explanation for the moderate efficacy of cetuximab in HNSCC (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the high fraction of protein overexpression, only 25% of samples in the TCGA-HNSC cohort were identified to have an active EGFR pathway. A recent phosphoproteomic study in HNSCC has identified that EGFR ligands rather than the receptor are the rate-limiting factor for EGFR pathway activity, offering an explanation for this discordance (33). This could be an explanation for the moderate efficacy of cetuximab in HNSCC (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Proteogenomics (the combination of genomics with proteomics) is also beginning to be utilized to toxicity and resistance to therapies and determine precision oncology strategies. The National Cancer Institute's Clinical Proteomic Tumor Analysis Consortium (CPTAC) has published several seminal manuscripts on various cancer types including pediatric brain cancer (56)(57)(58)(59)(60). We have found proteogenomics to be useful in identifying key pathways involved in metastatic progression to the brain (61).…”
Section: Future Directionsmentioning
confidence: 99%
“…For HPV-negative head and neck squamous cell carcinoma (Huang et al, 2021), three therapeutically actionable molecular subtypes were identified. The first subtype, high chromosome instability (CIN), showed the worst prognosis.…”
Section: Biological Insights From Proteogenomicsmentioning
confidence: 99%